ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKIAN DI WILAYAH BALI TIMUR - Wijaya, Gede Ngurah Wisnu Kesuma; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The problem of poverty continues to be a public discourse, the number of poor people from 2010 to 2019 shows that the largest number of poor people are in the East Bali region. The research objectives to be achieved are: 1) to simultaneously analyze the effects of economic growth, population growth, education, and unemployment on poverty in the East Bali region. 2) to partially analyze the effect of economic growth, population growth, education, and unemployment on poverty in the East Bali region. 3) to analyze the most dominant variable on poverty in the East Bali region. The data used in this research is secondary data. The data analysis technique used to solve the problem in this study is multiple linear regression analysis. The results of the analysis show that economic growth, population growth, education, and unemployment simultaneously have a significant effect on poverty levels in the East Bali region. Economic growth and education partially have a negative effect on poverty in the East Bali region. Population growth and unemployment partially have a positive effect on poverty in the East Bali region. Key words: poverty, economic growth, population growth, education, unemployment